2010
DOI: 10.1177/0734904110378974
|View full text |Cite
|
Sign up to set email alerts
|

Internal Fire Whirls in a Vertical Shaft

Abstract: Internal fire whirls induced by a pool fire in a vertical shaft of height 15 m with different ventilation conditions are studied experimentally. Ventilation is provided through a rectangular gap at the side wall with varying widths. Gasoline pool fires with diameters up to 0.46 m are set up at the center of the floor. Flame height and burning duration of the pool fire are measured. Average flame height ranged from 1 to 4.5 m when whirling is onsetted in the vertical shaft. Experimental studies indicate that ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 15 publications
2
37
0
Order By: Relevance
“…This suggests that, for small fire whirls, the flame height is circulation controlled, whereas for large fire whirls other parameters such as the burning rate and the buoyancy are also important. Chow et al (2010) also established a positive correlation between the fire whirl height and the product of the dimensionless fire powerQ * and pool diameter D 0 : H = 3.59Q * 2/5 D 0 . Byram & Martin (1962) and Lei et al (2011) have argued that the flame radius in the continuous flame region is nearly equal to that of the vortex core above the radial boundary layer (Byram & Martin 1962;Lei et al 2011).…”
Section: Heightmentioning
confidence: 99%
“…This suggests that, for small fire whirls, the flame height is circulation controlled, whereas for large fire whirls other parameters such as the burning rate and the buoyancy are also important. Chow et al (2010) also established a positive correlation between the fire whirl height and the product of the dimensionless fire powerQ * and pool diameter D 0 : H = 3.59Q * 2/5 D 0 . Byram & Martin (1962) and Lei et al (2011) have argued that the flame radius in the continuous flame region is nearly equal to that of the vortex core above the radial boundary layer (Byram & Martin 1962;Lei et al 2011).…”
Section: Heightmentioning
confidence: 99%
“…A fire whirl can be generated by burning a pool fire in a vertical shaft model of appropriate gap widths [11][12][13][14][15]20]. Such experiments were carried out to investigate the effect of the gap width on IFW generation.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…An IFW has a fixed physical fire size, and does not spread over the fuel surface as in open space. An IFW can be created in a vertical shaft in tall buildings with appropriate sidewall ventilation arrangement [11][12][13][14][15]. This is hazardous to green buildings with tall shafts or good thermal insulation [16][17][18] and studied as a long-term project.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a series of small to medium-scale vertical shaft fire whirl experiments has been carried out by Chow, Zou and co-workers [5][6][7]. It was demonstrated that the generation of fire whirl could be sub-divided into four stages including (i) initial ignition stage where the flame height is relatively low; (ii) flame rising-up stage where the flame height increase gradually to reach its upcoming state; (iii) stable whirling stage where the flame height is considered to be at its maximum height; (iv) decaying stage where the whirling motion stops and the fire gradually extinguishes.…”
Section: Introductionmentioning
confidence: 99%